A study of drinking water quality in Perlis - Nurazilah Ab. Karim (School of Environmental Engineering , University Malaysia Perlis, 2010)
Quality drinking water is an important aspect that needs to be emphasized. Realizing the importance of drinking water quality, the study of drinking water quality in Perlis was conducted. This study focuses on the quality of treated water that supplied for domestic use in Perlis. Sample of treated water are taken from the selected end user in Perlis. Four sampling points have been selected which is at Kuala Perlis, Kg. Padang Malau, Chuping, and Arau.